THE PLACE OF PSYCHOLOGY IN THE SYSTEM OF SCIENCES. - Sotiboldiyeva , Mokhinur (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
The article presents sources about the place of psychology in the interdisciplinary system of sciences. Psychology as an integral and independent science contributes to the formation of a humanistic worldview in people. Its connection with the human factor determines its direct relationship with all sciences that study human-related issues to a certain extent. First of all, these are social sciences and humanities, among which psychology holds a unique and leading position.